2024
DOI: 10.24084/repqj10.521
|View full text |Cite
|
Sign up to set email alerts
|

La0,6Sr0,4CoO3 Coating on AISI 430 Ferritic Stainless Steel for Application in ITSOFC Interconnects

Abstract: In order to restrain the high temperature oxidation on metallic interconnects, a ceramic coating is deposited on its surface. For this study a AISI 430 stainless steel was coated with perovskite (La 0,6 Sr 0,4 CoO 3 ) film using the spray pyrolysis technique. Therefore, in this work, the coating morphology and composition was evaluated through X-Ray diffraction and scanning electron microscopy/energy dispersive spectroscopy analyses. The oxidation behavior was also investigated by a high temperature oxidation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
1
0
0
Order By: Relevance
“…The oxide scale growth rate is calculated by Equation 1, where M is the sample mass gain, A is the sample surface area, t is the oxidation time and Kp is the parabolic rate constant. The result of parabolic rate constant (Kp) ( Table 4) of the bare sample is consistent with values presented in studies in the literature [31][32][33] . It is observed that the Kp results (Table 4) are similar for all the samples, which demonstrate that the formation of oxide was not influenced by the difference in surface samples.…”
Section: Resultssupporting
confidence: 77%
“…The oxide scale growth rate is calculated by Equation 1, where M is the sample mass gain, A is the sample surface area, t is the oxidation time and Kp is the parabolic rate constant. The result of parabolic rate constant (Kp) ( Table 4) of the bare sample is consistent with values presented in studies in the literature [31][32][33] . It is observed that the Kp results (Table 4) are similar for all the samples, which demonstrate that the formation of oxide was not influenced by the difference in surface samples.…”
Section: Resultssupporting
confidence: 77%